Tissue Expression Analysis, Cloning, and Characterization of the 5′-Regulatory Region of the Bovine LATS1 Gene - Wei, Dawei; Raza, Sayed Haidar Abbas; Wang, Xingping; Khan, Rajwali; Lei, Zhaoxiong; Zhang, Guijie; Zhang, Jiupan; Luoreng, Zhuoma; Ma, Yun; Alamoudi, Muna O.; Aloufi, Bandar Hamad; Alshammari, Ahmed Mohajja; et al. (Frontiers in Veterinary Science, 2022)
As a member of the large tumor suppressor gene (LATS) family, LATS1 plays an important role in regulating muscle growth and development. In the present study, we determined the distinct exhibit patterns of tissue expression and intracellular localization of bovine LATS1. Further, we obtained 1.7-kb of the 5’ regulatory region and the functional proximal minimal promoter of bovine LATS1 and identified the key transcription factors in the promoter region to elucidate its molecular regulation mechanism. The result showed that bovine LATS1 was highly expressed in the longissimus thoracis and up-regulation in infancy muscle and that its protein localizes to both the cytoplasm and the nucleus. An electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation (ChIP) assay in combination with site-directed mutation and siRNA interference demonstrated that Myod1 and MEF2A binding in the core promoter region (-298/-123bp) and play important roles in the transcriptional regulation of the bovine LATS1 promoter. Taken together, these interactions provide insight into the regulatory mechanisms of LATS1 transcription in mediating skeletal muscle growth in cattle.